Cognitive science of religion: what is it and why is it? - Barrett, J (Blackwell Publishing Ltd., 2007)
Cognitive science of religion brings theories from the cognitive sciences to bear on why religious thought and action is so common in humans and why religious phenomena take on the features that they do. The field is characterized by a piecemeal approach, explanatory non-exclusivism, and methodological pluralism. Topics receiving consideration include how ordinary cognitive structures inform and constrain the transmission of religious ideas, why people believe in gods, why religious rituals and prayer tend to have the forms that they do, why afterlife beliefs are so common, and how human memory systems influence socio-political features in religious systems. Cognitive Science of Religion is often associated with evolutionary science and anti-religious rhetoric but neither is intrinsic nor necessary to the field.